Effectiveness of Torbangun Leaf Soup in Increasing Breast Milk Production in Breastfeeding Women in Dince Safrina Pratama Clinic, Pekanbaru City - Berliana Irianti (Institute Of Computer Science (IOCS), 2021)
Breast milk (ASI) is not smooth or slightly thickened due to several variables, one of which is nursing and the awareness of the mother. The fewer frequently you breastfeed, the less milk you'll produce. The hormones prolactin and oxytocin aid in the production of breast milk. The less you breastfeed, the less milk you'll produce. As a result, many young mothers are concerned and fearful due to insufficient milk production. Greater secretion and production of breast milk stimulates protoplasmic activity in mammary gland secretory cells and secretory nerve endings, which results in increased milk secretion and is aided by the mechanism of action of laktagogums, or stimulates the lactagonist hormone prolactin. Lactation will be stimulated by mammary glands on alveolar epithelial cells. One of the attempts made in the problem of poor milk production is the use of galactagogum chemicals obtained from plants. Lactagogum (lactagogue) is one of the methods for increasing secretion and milk production. The goal of this study was to see how effective it was to boost breast milk production by giving people torbangun leaf soup. The study employed a one-group pretest-posttest design. This study took place in the Dince Safrina Pratama Clinic in Pekanbaru City from August 31 to October 7, 2020. The study's findings revealed that the p value for H0 was 0.008, indicating that H0 was rejected, and it was determined that Torbangun Leaf soup helped increase milk production in nursing women.